1999
DOI: 10.1029/1999gl005396
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for cessation of Indian Plate Subduction in the Burmese Arc Region

Abstract: Abstract.The issue of whether subduction is still active in the India-Burma plate boundary zone has been rather controversial. While the presence of an eastward dipping Indian lithospheric slab is undisputed, different opinions have been voiced regarding the continuance of subduction at present. Analysis of the Harvard CMT data in comparison with major subduction zones of the world demonstrates that the Burmese arc is a unique region where there is a subducted slab but the direction of plate motion is nearly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…The earlier seismologic studies suggested the cessation of subduction beneath the Burma Plate in the western Myanmar (e.g., Rao and Kumar, 1999) and no evidence of present-day active subduction to the north of the Andaman Islands, as it is shown by Table 1 Stratigraphy of the southern Chindwin Sub-Basin in the Central Myanmar Basin, and the stratigraphic intervals of the analyzed samples (modified after Aung Khin and Kyaw Win, 1969;Bender, 1983 Fossil rare, a palynological assemblage zone indicates the early Miocene (Reimann and Aye Thaung, 1981;Engelhardt, 1993) -…”
Section: Western Myanmar Subduction Zone: Andaman-arakan Trenchmentioning
confidence: 98%
“…The earlier seismologic studies suggested the cessation of subduction beneath the Burma Plate in the western Myanmar (e.g., Rao and Kumar, 1999) and no evidence of present-day active subduction to the north of the Andaman Islands, as it is shown by Table 1 Stratigraphy of the southern Chindwin Sub-Basin in the Central Myanmar Basin, and the stratigraphic intervals of the analyzed samples (modified after Aung Khin and Kyaw Win, 1969;Bender, 1983 Fossil rare, a palynological assemblage zone indicates the early Miocene (Reimann and Aye Thaung, 1981;Engelhardt, 1993) -…”
Section: Western Myanmar Subduction Zone: Andaman-arakan Trenchmentioning
confidence: 98%
“…In Myanmar, east of the Arakan Trench, the Arakan accretionary wedge is affected by shallow seismicity [ Dasgupta et al , 2003; Rao and Kumar , 1999; Satyabala , 2003] along large N/S strike‐slip faults [ Bender , 1983; Guzman‐Speziale and Ni , 1996; Socquet et al , 2002]. The Myanmar Central Basins bound this mountain belt to the east [ Bender , 1983; Pivnik et al , 1998; Rangin et al , 1999].…”
Section: Geodynamic Settingmentioning
confidence: 99%
“…Popa in Myanmar; both of which are believed to be either dormant or extinct (Curray 2005). Limited volcanic activity in this arc has been attributed either to the oblique nature of the subduction or to its complete cessation (e.g., Hurukawa et al 2012;Rao and Kumar 1999). From the volcanic history of the region, it is apparent that Barren Island volcano is the last of the active magmatic centers in the northern sector of the southwardly locking Sunda-Andaman subduction zone.…”
Section: Introductionmentioning
confidence: 96%